Analysis of the Influence of Load Unbalance on the Neutral Current Power Loss in Substation KP10 PT. PLN (Persero) UP3 Teluk Naga - Listiawati, Dwi; Pawenary; Apsari Nita Andini (Green Publisher, 2023)
The research objective is to analyze the percentage value of load unbalance before and after load balancing and the effect on neutral current losses. The load imbalance that occurs at the KP10 substation is simulated through the ETAP 16.0.0 software. Based on the research results, it was found that there was an imbalance in the load of the KP10 substation in direction B, which experienced the greatest load imbalance with a percentage of 38.76% and in direction A, which experienced a load imbalance of 19.6%. Based on SPLN No. 017 of 2014, the percentage of load imbalance exceeding 25% must be repaired. So that the repair is carried out by equalizing the load by breaking the load from direction B to direction A. After the activity of equalizing the load distribution, a decrease in the percentage of load imbalance is obtained. Majoring A is 8.9% and majoring B is 12,6%. The existence of this load imbalance also causes losses due to neutral currents where before the equalization activities the neutral current losses amounted to 6.99% and after the equalization of 1.06%. A simulation was also carried out where the load imbalance simulation results were obtained with the measurement results having results that were not much different.